Current diagnosis & treatment in otolaryngology head & neck surgery - Lalwani, Anil K.; Lalwani, Anil K. (New York : McGraw Hill Medical, 2012)
"A concise, one-stop clinician's guide for treating all major diseases of the ear, nose, throat, and neck. Conveniently organized by anatomic region. Constistent presentation includes General Considerations, Pathogenesis, Prevention, Clinical Findings, Differential Diagnosis, and Treatment. Must-know medical and surgical management of each disorder. Thorough discussion of pathophysiology and relevant basic and clinical science. More than 400 state-of-the-art clinical photographs and line drawings. Comprehensive radiology chapter with more than 150 images. 'Essentials of Diagnosis' section for each disease and disorder delivers key points at a glance"--P. 4 of cover.
"A Lange medical book."
"1545-6307"--T.p. verso.
Includes bibliographical references and index.
All age.
Keywords: Otolaryngology; Otolaryngology -- Diagnosis; Otolaryngology -- Treatment; Otorhinolaryngologic Diseases -- diagnosis; Otorhinolaryngologic Diseases -- therapy; Otorhinolaryngologic Surgical Procedures -- methods